2018
DOI: 10.4038/sljfmsl.v9i2.7809
|View full text |Cite
|
Sign up to set email alerts
|

Deaths on rail roads: a study from Colombo North Teaching Hospital, Sri Lanka

Abstract: In Sri Lanka railway related deaths are reported throughout the year. Most accidental deaths occur due to negligent behaviour of pedestrians and drivers. Fatal train impacts cause extensive visceral and musculoskeletal injuries due to the nature of the object as well as the amount of force transmitted during impact. A study of this nature would help ascertain demographic details of victims, characteristics of the incident of fatal train crashes and recognize the injury profile. An autopsy based retrospective s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 7 publications
(14 reference statements)
2
6
1
Order By: Relevance
“…Decapitation was seen in 40% of suicidal cases and in 7.4% of accidental deaths. This was contrast with the study 5 The present study showed a large proportion of accidental deaths (91.5%) compared to suicidal deaths (8.5%). There were no homicidal deaths.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Decapitation was seen in 40% of suicidal cases and in 7.4% of accidental deaths. This was contrast with the study 5 The present study showed a large proportion of accidental deaths (91.5%) compared to suicidal deaths (8.5%). There were no homicidal deaths.…”
Section: Discussioncontrasting
confidence: 99%
“…There were no homicidal deaths. A similar finding was observed by other studies 5,8 .However, these findings were contrary to the study carry out in New York, where suicide outnumbered to accidents 12 . Accidental deaths are often preventable with a great deal of good involvement of public and investigating authorities as seen in other studies.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations